World Library  
Flag as Inappropriate
Email this Article

Conway chained arrow notation

Article Id: WHEBN0000305456
Reproduction Date:

Title: Conway chained arrow notation  
Author: World Heritage Encyclopedia
Language: English
Subject: Knuth's up-arrow notation, Large numbers, Pentation, Steinhaus–Moser notation, Googolplex
Collection: Large Numbers, Mathematical Notation
Publisher: World Heritage Encyclopedia
Publication
Date:
 

Conway chained arrow notation

Conway chained arrow notation, created by mathematician John Horton Conway, is a means of expressing certain extremely large numbers in googology. It is simply a finite sequence of positive integers separated by rightward arrows, e.g. 2 → 3 → 4 → 5 → 6.

As with most combinatorial symbologies, the definition is recursive. In this case the notation eventually resolves to being the leftmost number raised to some (usually enormous) integer power.

Contents

  • Definition and overview 1
  • Properties 2
  • Interpretation 3
  • Examples 4
    • Systematic examples 4.1
  • Ackermann function 5
  • Graham's number 6
  • See also 7
  • References 8
  • External links 9

Definition and overview

A Conway chain (or chain for short) is defined as follows:

  • Any positive integer is a chain of length 1.
  • A chain of length n, followed by a right-arrow → and a positive integer, together form a chain of length n+1.

Any chain represents an integer, according to the four rules below. Two chains are said to be equivalent if they represent the same integer.

If p and q are positive integers, and X is a subchain, then:

  1. An empty chain (or a chain of length 0) represents 1, and the chain p represents the number p.
  2. p \to q represents the exponential expression p^q. (Note that Conway in [1] leaves the 2-tuple undefined, but has the 3d parameter count Knuth's arrows, so that this rule actually follows from the axiom to drop the \to 1 from the right end.)
  3. X \to 1 is equivalent to X.
  4. X \to p \to (q + 1) is equivalent to X \to ( X \to ( \cdots (X \to ( X ) \to q)\cdots ) \to q ) \to q
    (with p copies of X, p − 1 copies of q, and p − 1 pairs of parentheses; applies for q > 0).

Note that the last rule can be restated recursively to avoid the ellipses:

4a. X \to 1 \to (q + 1) = X
4b. X \to (p + 1) \to (q + 1) = X \to (X \to p \to (q+1)) \to q

Properties

  1. A chain of length 3 corresponds to hyperoperation and Knuth's up-arrow notation:
    \begin{matrix} p \to q \to r = p [r+2] q = p \!\!\! & \underbrace{ \uparrow\uparrow\uparrow \dots \uparrow\uparrow\uparrow } & \!\!\! q = p\uparrow^r q.\\ & \!\!\! r \text{ arrows} \!\!\! \end{matrix}
  2. a chain X → Y is of the form X → p; hence:
  3. a chain starting with a is a power of a
  4. a chain 1 → Y is equal to 1
  5. a chain X → 1 → Y is equal to X
  6. a chain 2 → 2 → Y is equal to 4
  7. a chain X → 2 → 2 is equal to X → (X) (chain X with its value concatenated to it)

Interpretation

One must be careful to treat an arrow chain as a whole. Arrow chains do not describe the iterated application of a binary operator. Whereas chains of other infixed symbols (e.g. 3 + 4 + 5 + 6 + 7) can often be considered in fragments (e.g. (3 + 4) + 5 + (6 + 7)) without a change of meaning (see associativity), or at least can be evaluated step by step in a prescribed order, e.g. 34567 from right to left, that is not so with Conway's arrow.

For example:

  • 2\rightarrow3\rightarrow2 = {}^32 = 2^{2^2} = 16
  • 2\rightarrow\left(3\rightarrow2\right) = 2^{(3^2)} = 2^{3^2} = 512
  • \left(2\rightarrow3\right)\rightarrow2 = \left(2^3\right)^2 = 64

The fourth rule is the core: A chain of 3 or more elements ending with 2 or higher becomes a chain of the same length with a (usually vastly) increased penultimate element. But its ultimate element is decremented, eventually permitting the third rule to shorten the chain. After, to paraphrase Knuth, "much detail", the chain is reduced to two elements and the second rule terminates the recursion.

Examples

Examples get quite complicated quickly. Here are some small examples:

n

= n (by rule 1)

p→q

= pq (by rule 2)
Thus 3→4 = 34 = 81

1→(any arrowed expression)

= 1 since the entire expression eventually reduces to 1number = 1. (Indeed, any chain containing a 1 can be truncated just before that 1; e.g. X→1→Y=X for any (embedded) chains X,Y.)

4→3→2

= 4→(4→(4)→1)→1 (by 4) and then, working from the inner parentheses outwards,
= 4→(4→4→1)→1 (remove redundant parentheses (rrp))
= 4→(4→4)→1 (3)
= 4→(256)→1 (2)
= 4→256→1 (rrp)
= 4→256 (3)
= 4256 (2)
= 13 407 807 929 942 597 099 574 024 998 205 846 127 479 365 820 592 393 377 723 561 443 721 764 030 073 546 976 801 874 298 166 903 427 690 031 858 186 486 050 853 753 882 811 946 569 946 433 649 006 084 096 exactly ≈ 1.34078079299 × 10154

2→2→4

= 2→(2)→3 (by 4)
= 2→2→3 (rrp)
= 2→2→2 (4, rrp)
= 2→2→1 (4, rrp)
= 2→2 (3)
= 4 (2) (In fact, any chain beginning with two 2s stands for 4.)

2→4→3

= 2→(2→(2→(2)→2)→2)→2 (by 4) The four copies of X (which is 2 here) are in bold to distinguish them from the three copies of q (which is also 2)
= 2→(2→(2→2→2)→2)→2 (rrp)
= 2→(2→(4)→2)→2 (previous example)
= 2→(2→4→2)→2 (rrp) (expression expanded in next equation shown in bold on both lines)
= 2→(2→(2→(2→(2)→1)→1)→1)→2 (4)
= 2→(2→(2→(2→2→1)→1)→1)→2 (rrp)
= 2→(2→(2→(2→2)))→2 (3 repeatedly)
= 2→(2→(2→(4)))→2 (2)
= 2→(2→(16))→2 (2)
= 2→65536→2 (2,rrp)
= 2→(2→(2→(...2→(2→(2)→1)→1...)→1)→1)→1 (4) with 65535 sets of parentheses
= 2→(2→(2→(...2→(2→(2))...))) (3 repeatedly)
= 2→(2→(2→(...2→(4))...))) (2)
= 2→(2→(2→(...16...))) (2)
= 2^{2^{\dots^2}} (a tower with 216 = 65536 stories)
= 655362 (See tetration)

2→3→2→2

= 2→3→(2→3)→1 (by 4)
= 2→3→8 (2 and 3)
= 2→(2→2→7)→7 (1)
= 2→4→7 (two initial 2's give 4 [prop6])
= 2→(2→(2→2→6)→6)→6 (4)
= 2→(2→4→6)→6 (prop6)
= 2→(2→(2→(2→2→5)→5)→5)→6 (4)
= 2→(2→(2→4→5)→5)→6 (prop6)
= 2→(2→(2→(2→(2→2→4)→4)→4)→5)→6 (4)
= 2→(2→(2→(2→4→4)→4)→5)→6 (prop6)
= 2→(2→(2→(2→(2→(2→2→3)→3)→3)→4) →5)→6 (4)
= 2→(2→(2→(2→(2→4→3)→3)→4)→5)→6 (prop6)
= 2→(2→(2→(2→(2→65536→2)→3)→4)→5)→6 (previous example)
= much larger than previous number

3→2→2→2

= 3→2→(3→2)→1 (4)
= 3→2→9 (2 and 3)
= 3→3→8 (4)

Systematic examples

The simplest cases with four terms (containing no integers less than 2) are:

  • a \to b \to 2 \to 2
    = a \to b \to 2 \to (1 + 1)
    = a \to b \to (a \to b) \to 1
    = a \to b \to a^b
    = a [a^b + 2] b
(also following from the last-mentioned property)
  • a \to b \to 3 \to 2
    = a \to b \to 3 \to (1 + 1)
    = a \to b \to (a \to b \to (a \to b) \to 1) \to 1
    = a \to b \to (a \to b \to a^b)
    = a [a\to b \to 2 \to 2 + 2] b
  • a \to b \to 4 \to 2
    = a \to b \to (a \to b \to (a \to b \to a^b))
    = a [a \to b \to 3 \to 2 + 2] b

We can see a pattern here. If, for any chain X, we let f(p) = X \to p then X \to p \to 2 = f^p(1) (see functional powers).

Applying this with X = a \to b, then f(p) = a [p + 2]b and a \to b \to p \to 2 = a [a \to b \to (p - 1) \to 2 + 2] b = f^p(1)

Thus, for example, 10 \to 6 \to 3\to 2 = 10 [10 [1000002] 6 + 2] 6 \!.

Moving on:

  • a \to b \to 2 \to 3
    = a \to b \to 2 \to (2 + 1)
    = a \to b \to (a \to b) \to 2
    = a \to b \to a^b \to 2
    = f^{a^b}(1)

Again we can generalize. When we write g_q(p) = X \to p \to q we have X \to p \to q+1 = g_q^p(1), that is, g_{q+1}(p) = g_q^p(1). In the case above, g_2(p) = a \to b \to p \to 2 = f^p(1) and g_3(p) = g_2^p(1), so a \to b \to 2 \to 3 = g_3(2) = g_2^2(1) = g_2(g_2(1)) = f^{f(1)}(1) = f^{a^b}(1)

Ackermann function

The Ackermann function may be expressed using Conway chained arrow notation:

A(m, n) = (2 → (n + 3) → (m − 2)) − 3 for m > 2 (Since A(m, n) = 2 [m] (n + 3) - 3 in hyperoperation)

hence

2 → nm = A(m + 2,n − 3) + 3 for n > 2

(n = 1 and n = 2 would correspond with A(m, −2) = −1 and A(m, −1) = 1, which could logically be added).

Graham's number

Graham's number G \! itself cannot be expressed concisely in Conway chained arrow notation, but by defining the intermediate function f(n) = 3 \rightarrow 3 \rightarrow n \!, we have: G = f^{64}(4)\, (see functional powers), and 3 \rightarrow 3 \rightarrow 64 \rightarrow 2 < G < 3 \rightarrow 3 \rightarrow 65 \rightarrow 2\,

Proof: Applying in order the definition, rule 3, and rule 4, we have:

f^{64}(1)\,

= 3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow (\cdots (3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow 1))\cdots ))\, (with 64 3 \rightarrow 3's)
= 3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow (\cdots (3 \rightarrow 3 \rightarrow (3 \rightarrow 3) \rightarrow 1) \cdots ) \rightarrow 1) \rightarrow 1\,
= 3 \rightarrow 3 \rightarrow 64 \rightarrow 2;\,

f^{64}(4) = G;\,

= 3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow (\cdots (3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow 4))\cdots ))\, (with 64 3 \rightarrow 3's)

f^{64}(27)\,

= 3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow (\cdots (3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow 27))\cdots ))\, (with 64 3 \rightarrow 3's)
= 3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow (\cdots (3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow (3 \rightarrow 3)))\cdots ))\, (with 65 3 \rightarrow 3's)
= 3 \rightarrow 3 \rightarrow 65 \rightarrow 2\, (computing as above).

Since f is strictly increasing,

f^{64}(1) < f^{64}(4) < f^{64}(27)\,

which is the given inequality.

With chain arrows it is very easy to specify a much larger number. For example, note that

3 \rightarrow 3 \rightarrow 3 \rightarrow 3 ~~ = ~~ 3 \rightarrow 3 \rightarrow (3 \rightarrow 3 \rightarrow 27 \rightarrow 2) \rightarrow 2\, ~~ = ~~ f^ {3 \rightarrow 3 \rightarrow 27 \rightarrow 2}(1) ~~ = ~~ f^{f^{27}(1)}(1)

which is much greater than Graham's number, because the number 3 \rightarrow 3 \rightarrow 27 \rightarrow 2 = f27(1) is much greater than 65.

See also

References

  1. ^ John H. Conway & Richard K. Guy, The Book of Numbers, 1996, p.59-62

External links

  • Factoids > big numbers
  • Robert Munafo's Large Numbers
  • The Book of Numbers by J. H. Conway and R. K. Guy
This article was sourced from Creative Commons Attribution-ShareAlike License; additional terms may apply. World Heritage Encyclopedia content is assembled from numerous content providers, Open Access Publishing, and in compliance with The Fair Access to Science and Technology Research Act (FASTR), Wikimedia Foundation, Inc., Public Library of Science, The Encyclopedia of Life, Open Book Publishers (OBP), PubMed, U.S. National Library of Medicine, National Center for Biotechnology Information, U.S. National Library of Medicine, National Institutes of Health (NIH), U.S. Department of Health & Human Services, and USA.gov, which sources content from all federal, state, local, tribal, and territorial government publication portals (.gov, .mil, .edu). Funding for USA.gov and content contributors is made possible from the U.S. Congress, E-Government Act of 2002.
 
Crowd sourced content that is contributed to World Heritage Encyclopedia is peer reviewed and edited by our editorial staff to ensure quality scholarly research articles.
 
By using this site, you agree to the Terms of Use and Privacy Policy. World Heritage Encyclopedia™ is a registered trademark of the World Public Library Association, a non-profit organization.
 


Copyright © World Library Foundation. All rights reserved. eBooks from Project Gutenberg are sponsored by the World Library Foundation,
a 501c(4) Member's Support Non-Profit Organization, and is NOT affiliated with any governmental agency or department.